OPTIMIZATION OF MECHANICAL STRENGTH OF ROTARY-VANE ENGINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The article discusses a rotory-vane heat engine with a lever-cam mechanism motion conversion (an engine may be an internal combustion or external combustion). The output shaft of the engine adds drive torque from the working fluid pressure forces acting on the blade and the inertial moment of the forces of inertia of engine components. The mechanical strength of the motor is dependent on the magnitude and phase of these two torque. The purpose of the article is to determine the conditions under which mechanical strength is minimized.